Adherence to medication in adults with Cystic Fibrosis: An investigation using objective adherence data and the Theoretical Domains Framework - Arden, Madelynne A. (Br J Health Psychol, 2019)
OBJECTIVES: Adherence to nebulizer treatment in adults with Cystic Fibrosis (CF) is poor, and interventions are needed. This research aimed to identify the factors affecting nebulizer adherence using the Theoretical Domains Framework (TDF) and to compare these for participants with different levels of adherence. DESIGN: Data‐prompted interviews using the TDF. METHODS: Eighteen semi‐structured interviews were conducted with adults with CF during which objectively measured adherence data were discussed. Framework analysis was used to code the data into TDF domains, and inductive qualitative content analysis was used to code different beliefs and experiences. Aspects of the TDF that differed between participants with different adherence levels were explored. RESULTS: Factors influencing adherence to treatment included all 14 domains of the TDF, 10 of which appeared to vary by adherence level: Skills; Memory and decision‐making; and Behavioural regulation; Environmental context and resources; Social influences; Beliefs about consequences; Beliefs about capability; Reinforcement; Social role and identify; Intentions; Optimism; and Emotions. CONCLUSIONS: This study is the first to use objectively measured adherence data in a data‐prompted interview using the TDF framework to systematically assess the full range of factors potentially influencing adherence. The results highlighted that interventions need to consider issues of capability, opportunity, and motivation. Interventions that challenge dysfunctional beliefs about adherence and which support the development of routines or habits and problem‐solving may be particularly useful for adults with CF. STATEMENT OF CONTRIBUTION: What is already known? Adherence to medication in adults with cystic fibrosis is poor. Previous research has identified a range of contributing factors in relation to subjective reports of adherence. There is a wide discrepancy between self‐reported adherence and objectively measured adherence. What this study adds A data‐prompted interview using objectively measured adherence data enabled the systematic assessment of potential factors that could be targeted in an intervention to increase adherence. There were some differences in the factors that were identified by high and low adherers. There is not one‐size fits all intervention for adherence to medication in cystic fibrosis.